Prevalence of functional dependence in Chinese centenarians and its relationship with serum vitamin D status - Yao Y (Dove Medical Press, 2018)
Yao Yao,1,* Shihui Fu,2,* Qiuling Shi,3 Hao Zhang,4 Qiao Zhu,5 Fu Zhang,5 Fuxin Luan,5 Yali Zhao,5 Yao He1 1Institute of Geriatrics, Beijing Key Laboratory of Aging and Geriatrics, National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Department of Geriatric Cardiology, Chinese PLA General Hospital, Beijing, People’s Republic of China; 3Department of Symptom Research, MD Anderson Cancer Center, Houston, TX, USA; 4Department of Health Policy and Management, Texas A&M University, College Station, TX, USA; 5Central Laboratory, Hainan Branch of Chinese PLA General Hospital, Sanya, People’s Republic of China *These authors contributed equally to this work Background: Functional dependence (FD) and vitamin D deficiency are common conditions in older adults. However, little is known about the relationship between FD and serum vitamin D status in centenarians. The current study was designed to evaluate the prevalence of FD and examine its relationship with serum vitamin D status among centenarians in China.Subjects and methods: A cross-sectional study of a large sample of Chinese centenarians including 180 men and 822 women was conducted from June 2014 to December 2016. Home interviews, physical examinations, and blood analyses were performed in 958 centenarians following standard procedures. FD was evaluated using the Barthel index of activities of daily living (ADL). Serum 25-hydroxyvitamin D (25OHD) concentrations were measured as a marker of vitamin D status.Results: The prevalence of centenarians with FD was 71.2%. Vitamin D deficiency, lack of tea consumption, lack of outdoor activities, visual impairment, and fracture were predictors of FD. Centenarians in the lowest quartile of serum 25OHD concentration had an approximately threefold greater likelihood of FD than those in the highest quartile in multiple logistic regression models (OR =2.88; 95% CI 1.75–4.73; P<0.001). The multivariable OR with a 1 ng/mL decrease in serum 25OHD concentration was 1.06 (95% CI 1.04–1.08; P<0.001) for FD.Conclusion: Serum 25OHD levels have important associations with FD in Chinese centenarians. Future research could focus on the value of intervening in the case of low serum 25OHD levels through vitamin D supplementation and improving ADL in the older population. Keywords: centenarians, China, functional dependence, vitamin D